Neighborhood racial/ethnic composition and depressive symptoms of later life: The moderation effects of individual race/ethnicity - Seungjong Cho, Ph.D.; Tyrone C. Hamler, Ph.D. (Archives of Gerontology and Geriatrics Plus, 2025)
Purpose: Existing research indicates a complex relationship between the racial/ethnic composition of neighborhoods, individuals' own race/ethnicity, and depressive symptoms. To fill this gap, this study aims to test whether race/ethnicity moderates the relationship between neighborhood racial/ethnic composition and depressive symptoms. Materials and Methods: This study used merged data from the Health and Retirement Study 2016 and the American Community Survey 2014–2018 Data (N = 5,241). This study applied a mixed-effects negative binomial regression model. Results: Non-Hispanic Black respondents tended to have higher counts of depressive symptoms, compared to non-Hispanic Whites. However, the moderation effect of individuals’ own race/ethnicity was significant for non-Hispanic Blacks. Specifically, non-Hispanic Blacks experienced lower predicted counts of depressive symptoms when living in neighborhoods with a higher proportion of Black residents, suggesting a protective effect of racial concordance. Discussion: These findings highlight the importance of considering the dynamics of depressive symptomatology and race at both the individual and neighborhood levels. Interventions targeting vulnerable older adults can be more effectively designed by incorporating individual and neighborhood racial contexts.